The Values of Islamic Education in The Tradition of Tolabalango and Madduta - Asiah, Siti (UIN Maulana Malik Ibrahim Malang, 2018)
Motolobalango and Madduta-Mamanu-manu customs in the courtship tradition of Gorontalo tribe and Bugis tribe have institutionalized in society. Motolobalango is carried out when the families of both parties have carried out dulohupa (meeting), while Madduta-Mamanu-manu is carried out when a boy proposes to a girl. These two customs have their own characteristics, yet in certain cases the process has similarities and differences. This study discusses the implementation of courtship tradition in Islamic perspective and analyses the values of Islamic education contained in this tradition. The values of Islamic education are the attributes inherent in education to achieve the purpose of human life, namely to serve God, the Almighty. The value in Islamic education is something which is helpful and useful for humans after undergoing a process of effort carried out consciously and intentionally, so that the behavior of a person or society changes from a certain state to a better state. The results of the analysis showed that courtship tradition contains the value of tolerance and cooperation, as well as social, economic and religious values. Tradisi Motolobalango dan Madduta-Mamanu-manu dalam adat peminangan suku Gorontalo dan masyarakat suku Bugis merupakan tradisi yang telah melembaga dalam kehidupan bermasyarakat. Proses Motolobalango dilakukan ketika keluarga kedua belah pihak telah melakukan dulohupa (perjumpaan). Sementara Madduta-Mamanu-manu dilakukan dalam meminang atau melamar gadis. Dua tradisi adat ini memiliki karakter yang dalam hal-hal tertentu prosesinya memiliki persamaan dan perbedaan. Kajian ini mengangkat tentang penyelenggaraan tradisi adat peminangan dalam perspektif Islam serta menganalisis nilai-nilai pendidikan Islam yang terkandung dalam tradisi tersebut. Nilai-nilai pendidikan Islam adalah sifat-sifat yang melekat pada pendidikan untuk mencapai tujuan hidup manusia yaitu mengabdi pada Allah SWT. Jadi, nilai dalam pendidikan Islam adalah sesuatu yang bermanfaat dan berguna bagi manusia setelah menjalani proses upaya yang dilakukan secara sadar dan sengaja sehingga perilaku seseorang atau masyarakat berubah dari keadaan tertentu ke suatu keadaan yang lebih baik. Hasil analisis menunjukkan bahwa tradisi peminangan tersebut memiliki nilai toleransi, kerjasama, sosial, ekonomi dan religi.